Dampak Pengetahuan Sosial Terhadap Pembentukan Identitas Nasional - Dhaifah Khairunnisa Bilge; M. Zalva Zakira; Rosa Yunita Sihombing; Sani Safitri (Indo Publishing, 2025)
Social knowledge has an important role in shaping Indonesia's national identity amidst ethnic, cultural, religious and linguistic diversity. Through understanding history, culture, national values, and the principle of Bhinneka Tunggal Ika, social knowledge helps people recognize, appreciate and strengthen national identity. This article discusses Social Knowledge as the Foundation of National Identity and Social Knowledge in Realizing National Unity. Apart from that, social knowledge also contributes to preventing social conflict by teaching peaceful problem solving and strengthening a sense of togetherness as one nation. With good social education, the younger generation can grow up with an awareness of the importance of maintaining national unity and national identity. Therefore, improving the quality of social education is a strategic step in building a nation that is harmonious, strong and based on the values ​​of diversity.